Characteristics of andragogic training programs and learning processes in peruvian mining safety - del Carmen Vallejo Romo, Lucila (2016)
The objective of this study is to present the andragogical model and its benefits in its application to safety training in Peruvian mining. Based on the andragogical characteristics, this thesis explains the andragogical principles, the importance of adult education, the difference between learning and teaching of children and adults, the characteristics of adults and learning methodological strategies for the effective training of miners. Safety training in this industry is a must for the acquisition of behaviors that can reduce the number of accidents and incidents at work. The investigation is of applied type and the explanatory level; the design responds to the non-experimental design, the population was made up of those responsible for the safety training programs, and the sample was represented by thirty-one training managers and eight andragogy experts. The techniques used in the study are the survey for those responsible for the training and the judgment of experts to assess the relevance of applying the andragogic model in the training of the Peruvian mining company. The statistical tool for the hypothesis test was the Chi Square corroborating the postulated hypothesis.